Jalan Menuju Tuhan: Revitalisasi dan Interpretasi Makna atas Penciptaan Karya Tari Shirath Nan Tersirat - Romi Nursyam; Abdul Fadhil (Universitas Negeri Jakarta, 2018)
This article is an elaboration of the creation of Sirat Nan Tersirat dance which is the result of a revitalization of the cultural phenomenon of Paninggahan people who still believe in mystical matters that is known to contradict the Islamic creed, namely to ask the gods or jin by glorifying a place in Nagari Paninggahan. The purpose of this work is to express a work of dance depicting human characters entering the unseen world and to create a work of dance that reflects the human character who wants to meet his Lord (Allah SWT). The creation of this dance is inspired by the story in the origin of the Adok dance in Nagari Paninggahan when a king (Rajo Bagombak Bagalang Leg, the descendant of Pagaruyuang's king) is possessed when hearing the voice of the singing of the gods. The writing uses two approaches, namely the scienceof dance and Islamic approaches. The choreographer gives reinterpretation, i.e. not a god or jinn that enters the human realm but the man who enters the realm of the jinn. In the process of creating, it tries to reinterpret the Adok dance in accordance with the teachings of Islam and the main theme is the road to God (Sirat).